Assessment of health utilities and quality of life in patients with non-alcoholic fatty liver disease. Issue 1 (1st August 2016) - Sayiner, Mehmet; Stepanova, Maria; Pham, Huong; Noor, Bashir; Walters, Mercedes; Younossi, Zobair M
Abstract : Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease associated with increased liver-related mortality. Additionally, NAFLD could potentially impair health-related quality of life. Although an approved treatment for NAFLD does not exist, a number of new drugs for treatment of NAFLD are being developed. As the efficacy and safety of these regimens are being established, their cost-effectiveness, which requires the use of quality of life metrics and health utility scores to quality-adjusted outcomes, must also be assessed. The aim of this study was to report quality of life and health utilities in patients with NAFLD with and without cirrhosis for future use. Methods: Patients with NAFLD were seen in an outpatient clinic setting. Each patient had extensive clinical data and completed the Short Form-36 (SF-36 V.1) questionnaire. The SF-6D health utility scores were calculated. Results: There were 89 patients with the spectrum of NAFLD completed the SF-36 questionnaire: 59 with non-cirrhotic NAFLD and 30 with cirrhosis. Patients with NAFLD had significantly lower quality of life and health utility scores than the general population (all p<0.0001). Furthermore, patients with cirrhosis had lower quality of life and utility scores than non-cirrhotic NAFLD patients: SF-6D 0.660±0.107 in non-cirrhotic NAFLD vs 0.551±0.138 in cirrhotic NAFLD (p=0.0003). Conclusions: Health utilities and quality of life scores are impaired in patients with cirrhotic NAFLD. These values should be used in cost-effectiveness analysis of the upcoming treatment regimens for advanced NAFLD.